Expression of prolactin receptors in normal, benign, and malignant breast tissue: an immunohistological study. Issue 12 (1st December 2001) - Gill, S; Peston, D; Vonderhaar, B K; Shousha, S
Abstract : Aims —Prolactin plays an important role in the proliferation and differentiation of normal breast epithelium, and possibly in the development of breast carcinoma. The effects of prolactin are mediated by its receptor; thus, alteration in the expression of this receptor could be important in studying the biology of breast cancer. This investigation was aimed at comparing the expression of prolactin receptors in normal, benign, and malignant breast tissue. Material/Methods —The expression of prolactin receptors was studied in paraffin wax embedded sections of 102 breast biopsies (93 female and nine male), using the monoclonal antibody B6.2, and the avidin–biotin immunoperoxidase technique. Six biopsies were normal, 34 had benign lesions, and 62 were malignant. Results —In normal cases, prolactin receptor positivity was seen only on the luminal borders of the epithelial cells lining ducts and acini. In most benign lesions, variable degrees of luminal and cytoplasmic staining were seen. Cells showing apocrine metaplasia and florid regular ductal epithelial hyperplasia were mostly negative. In malignant cases, the staining pattern was mostly cytoplasmic and heterogeneous. Forty one of the 59 carcinomas in women showed a degree of positivity involving 10–100% of the tumour cells. A significant direct correlation was found between prolactin receptor and oestrogen receptor staining when only cases that scored more than 100/300 for the latter receptor, using the H scoring system, were considered (p = 0.0207). No correlation was found between prolactin receptors and progesterone receptors, patient's age, tumour size, tumour grade, or axillary lymph node status. Conclusions —Prolactin receptors seem to be expressed at different cellular sites in normal, benign, and malignant breast epithelial cells. The receptor is expressed in more than two thirds of female breast carcinomas, suggesting that it may play a role in the pathogenesis of the disease. The positivity is correlated with moderate and strong staining for oestrogen receptors in tissue sections, but not with other prognostic factors.